Nowcasting modified domestic demand using monthly indicators - Paul Egan (The Economic and Social Research Institute (ESRI), 2021)
The COVID-19 pandemic has highlighted the need for timely information on the evolving economic impacts of such a crisis. During these periods, there is an increased need to understand the current state of the economy in order to guide the effective implementation of policy. This is made difficult by the fact that official estimates of economic indicators, such as those published in the CSO's Quarterly National Accounts (QNA), are released with a substantial lag. This working paper shows that the information contained in a large number of monthly Irish economic indicators can be related to the official statistics of the QNA, namely Modified Domestic Demand (MDD), under the methodological framework of a dynamic factor model (DFM). The paper indicates that this methodology can be applied not only to nowcast quarterly MDD, but also to compute the dynamics of Irish economic activity at a monthly level. This monthly indicator can in turn be decomposed so that the contribution of each sub-category can be examined. The paper also suggests that accounting for structural breaks improves the nowcasting performance of MDD.
Keywords: 330